Comparison of Water Conditions and Growth Performance of Vannamei Shrimp (Litopenaeus vannamei) under Different Pond Management Systems (Superintensive, Intensive, and Traditional Culture Systems) - Sri Astutik; Sri Andayani; Asus Maizar Suryanto Hertika (Postgraduate, University of Mataram, 2025)
Vannamei shrimp (Litopenaeus vannamei) is one of the high-value aquaculture commodities in the global market, known for its excellent adaptability to various environmental conditions, rapid growth, and high survival rates. This study aims to compare water conditions and the growth performance of vannamei shrimp under three different pond management systems: supra-intensive, intensive, and traditional. The analysis was conducted by measuring water quality parameters such as temperature, salinity, pH, dissolved oxygen, ammonia, and nitrate concentrations. Growth performance was evaluated through observations of Average Daily Gain (ADG) and Mean Body Weight (MBW). At 50 days of cultivation, the supraintensive system produced an average body weight of 11.85 grams with a daily growth rate of 0.2219 grams/shrimp/day. The intensive system resulted in slightly lower growth, with an average body weight of 8.6 grams and a daily growth rate of 0.1547 grams/shrimp/day. The traditional system showed the lowest growth performance, with an average weight of 6.66 grams and an ADG of 0.0265 grams/shrimp/day. The different pond management systems influence the dynamic risks of water quality changes based on input loads from feed waste and feces. The traditional system exhibits a slower rate of water quality changes compared to the intensive and supraintensive systems.